Natural Disasters and Food Crises in Low-Income Countries : Macroeconomic Dimensions - Adedeji, Olumuyiwa; Bricco, Jana.; Kehayova, Vera. (Washington, D.C. : International Monetary Fund, 2016)
The exposure of low-income countries to natural disasters has a significant impact on food production and food security. This paper provides a framework for assessing a country's vulnerability to food crisis in the event of natural disasters. The paper finds that macroeconomic and structural indicators that are crucial for ensuring the resilience of low-income countries to adverse external shocks are equally important for minimizing the occurrence of food crisis in the event of natural disasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet